Flavonoid Derivative of Cannabis Demonstrates Therapeutic Potential in Preclinical Models of Metastatic Pancreatic Cancer - Moreau, Michele; Ibeh, Udoka; Decosmo, Kaylie; Bih, Noella; Yasmin-Karim, Sayeda; Toyang, Ngeh; Lowe, Henry; Ngwa, Wilfred (Frontiers in Oncology, 2019)
Pancreatic cancer is particularly refractory to therapy, with a current dismal five-year survival rate for patients of about 8%. One of the significant barriers to effective treatment is the immunosuppressive pancreatic tumor microenvironment and development of resistance to treatment. New treatment options to increase survival and quality of life of patients are urgently needed. This study reports on a new non-cannabinoid, non-psychoactive derivative of cannabis, called FBL-03G, with the potential to treat pancreatic cancer. In-vitro results show major increase in apoptosis and consequential decrease in survival for different pancreatic cancer models: Panc-02 and KPC pancreatic cancer cells treated with varying concentrations of FBL-03G and radiotherapy. Meanwhile, in-vivo results demonstrate therapeutic efficacy in delaying both local and metastatic tumor progression in animal models with pancreatic cancer when using FBL-03G sustainably delivered from smart radiotherapy biomaterials. Repeated experiments also showed significant (P < 0.001) increase in survival for animals with pancreatic cancer compared to control cohorts. The findings demonstrate potential for this new cannabis derivative in treatment of both localized and advanced pancreatic cancer, providing impetus for further studies towards clinical translation.